New Headway. Advanced Teacher's Book - Soars L. Liz (Oxford, Oxford University Press, 2003)
Headway is the course teachers and learners can rely Why? An authoritative integrated syllabus, motivating ics, and clearly focused tasks, combine with a real Jerstanding of what works in the classroom. It all makes effective teaching and effective learning.Tried and ested all over the world, it's probably the most popular irse ever written! In theTeacher's Book, full support for the teacher with any tricky questions. Hints and ideas for preparation and remedial work How to deal with likely problems and common errors Additional photocopiable materials, Stop and Check reviews, and Progress Tests.